2017
DOI: 10.1002/hpm.2448
|View full text |Cite
|
Sign up to set email alerts
|

Elements of a sustainable, competent, and empathetic workforce to support patients with dementia during an acute hospital stay: A comprehensive literature review

Abstract: Internationally, there has been a focus on the development of acute hospital workforces to support and care for people with dementia. Recommendations and initiatives to improve person-centred care in acute hospitals have included: education and training, dementia-specific roles, clinical leads, and environment changes. The aim of this literature review is to understand the elements of a sustainable, competent, and empathetic acute hospital workforce providing person-centred care for patients with dementia. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…Patients with dementia rely upon hospital staff to maintain their wellbeing (Brooke & Semlyen, 2017;Dewing & Dijk, 2016;Digby & Bloomer, 2014;Edvardsson, Sandman, & Rasmussen, 2011), though the skills required of hospital staff are not demonstrated routinely or consistently (Cowdell, 2010;Dewing & Dijk, 2016;Digby et al, 2017;Goldberg et al, 2014;Griffiths, Knight, Harwood, & Gladman, 2014;Handley et al, 2017;Moyle, Borbasi, Wallis, Olorenshaw, & Gracia, 2010). It is not known how the widely-recommended emotion-focused approaches (Brooker & Surr, 2006;Feil, 1993;Kitwood, 1997) translate into hospital care (Dewar & Nolan, 2013;Edvardsson et al, 2011;Scerri et al, 2015); in part this is due to the culture of hospitals the complex systems of rules and order within hospitals (Street & Coleman, 2012) (Brooke & Ojo, 2017;Handley et al, 2017). In a review of all dementia care training interventions for hospital staff, Scerri et al (2017) found an absence of emotion-orientated training and reported that the wellbeing and emotions of patients were not evaluated as an outcome in any study.…”
Section: Responses To Emotional Distress By Hospital Care Staffmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with dementia rely upon hospital staff to maintain their wellbeing (Brooke & Semlyen, 2017;Dewing & Dijk, 2016;Digby & Bloomer, 2014;Edvardsson, Sandman, & Rasmussen, 2011), though the skills required of hospital staff are not demonstrated routinely or consistently (Cowdell, 2010;Dewing & Dijk, 2016;Digby et al, 2017;Goldberg et al, 2014;Griffiths, Knight, Harwood, & Gladman, 2014;Handley et al, 2017;Moyle, Borbasi, Wallis, Olorenshaw, & Gracia, 2010). It is not known how the widely-recommended emotion-focused approaches (Brooker & Surr, 2006;Feil, 1993;Kitwood, 1997) translate into hospital care (Dewar & Nolan, 2013;Edvardsson et al, 2011;Scerri et al, 2015); in part this is due to the culture of hospitals the complex systems of rules and order within hospitals (Street & Coleman, 2012) (Brooke & Ojo, 2017;Handley et al, 2017). In a review of all dementia care training interventions for hospital staff, Scerri et al (2017) found an absence of emotion-orientated training and reported that the wellbeing and emotions of patients were not evaluated as an outcome in any study.…”
Section: Responses To Emotional Distress By Hospital Care Staffmentioning
confidence: 99%
“…First, this study provided the detail of achievable care, recognising the existing knowledge of hospital staff, and such research has been called for (Brooke & Ojo, 2017;Dewing & Dijk, 2016). Importantly, the findings offered are solutions from practice, which responds to prior criticism of an overemphasis on theoretical models of person-centred care for patients with dementia when in hospital (Dewing & Dijk, 2016).…”
Section: Strengthsmentioning
confidence: 99%
“…This shorthand is consistent with expert thinking that has been refined over time, as compared with staff newer to the profession who make decisions more slowly and are influenced by more information,27 such as that relating to each individual patient. Traditional training in dementia care has prioritised medical care,5 which reflects the approach prioritised here by longer-standing staff. In this study, staff with more years of professional experience tended to describe behaviour as agitation or aggression and were more likely to list medical causes of emotional distress such as infection or delirium, which suggests an approach that overlooks the complexity of a person beyond diagnostic criteria 28.…”
Section: Discussionmentioning
confidence: 99%
“…This is because a personal perspective can tailor care to address what matters most for the patient and can therefore improve health outcomes 2. These benefits are urgently needed in hospital care for patients with dementia, which has been addressed as an international priority3 4 and has been criticised for being task-orientated and falling short of person-centred care 5 6. By person-centred care, we mean that which meets the holistic needs of the patient as a person, who shares the same value and humanness as any other person 7 8.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation